Contextualization of the Understanding of Qur'an Verses for Social Education - MZ, Ahmad Murtaza; Ritonga, Abdullah Sani; ‘Aqila, Rosyda (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2024)
The reading of the Qur'an universally reveals a more complex and contextual meaning related to social education. This research aims to contextualize the values of social education contained in the Qur'an as a whole. Qualitative methods are used in this study, with content analysis as the main analytical tool for the data presented. The primary data sources used are Qur'anic verses that have a social education dimension, while secondary data include theses, articles, dissertations, and other documents relevant to this research. The results of this study show that the social education contained in the Qur'an focuses not only on improving the quality of individuals, but also society as a whole. This goal can be achieved through guidance and internalization of the teachings of social education contained in the Qur'an from an early age. This research also shows that the universal reading of the Qur'an can reveal more complex mechanisms of understanding, which significantly enriches the understanding of the social educational values contained in it.